ACTIVE LEARNING MODELS INCREASE CADET ACADEMIC VALUE - Sabam Danny Sulung; Ahmad Mubarok; Rifki Arif; Arief Rusdiansyah; Ahmad Hariri (SOSIOEDUKASI, 2020)
Learning activities should engage students to be active, but each educator has a different teaching style. However, many students are still not paying attention to the learning process because they are bored or less interested in the lessons learned. This study's objectives are to (1) know the results of cadet study in the course of ground handling State Polytechnic of Banyuwangi; (2) know the difference in cadet learning results in ground handling courses at State Polytechnic of Banyuwangi using active learning methods. This type of research is Class Action Research (PTK). This research is included in the research design of one group pretest-posttest. This research was conducted in the State Polytechnic of Banyuwangi. The data analysis technique used is a different test. The analysis results can be concluded that the application of active learning can improve cadet learning results in ground handling courses in State Polytechnic of Banyuwangi. This finding is evidenced by a significant difference in the pre-test and post-test learning outcomes. Students' learning outcomes are significantly higher after active learning applications than students' learning outcomes before applying active learning in ground handling courses.